Natural Therapies of the Inflammatory Bowel Disease: The Case of Rutin and its Aglycone, Quercetin - Habtemariam, Solomon; Belai, Abebech (Mini Reviews in Medicinal Chemistry, 2018)
Inflammatory bowel disease (IBD), commonly represented by ulcerative colitis and Crohn's disease, is a form of chronic inflammatory disorders of the gastrointestinal system. Its current drug treatment includes the use of antibiotics, 5-aminosalicylates, corticosteroids, immune-modifying agents and biologics such as anti-TNF agents and adhesion molecules blockers. These drugs have inherent problems of efficacy as many IBD sufferers need surgical intervention at some stage, high cost especially for the protein-based drugs, loss of efficacy and unwanted side effects. The discovery of novel drugs including those from natural sources that overcome the above mentioned drawbacks of the current therapy is therefore of great interest. While the flavonoid quercetin with proven antiinflammatory effect failed to show activity in vivo, its glycoside rutin has recently proven to possess a significant IBD therapeutic potential in experimental animals. In this communication, the pharmacological and pharmacokinetic profiles of rutin along with its ability to serve as a prodrug that deliver the bioactive quercetin close to the IBD site are discussed. Potential mechanisms of action far beyond antioxidant effects such as suppression of proinflammatory mediators' release and expression of inflammatory proteins (e.g. adhesion molecules, cyclooxygenase, nitric oxide synthase, etc.) are also scrutinized.
Keywords: rutin